THE LIBERALIZATION OF CIVIL AVIATION SAFETY: PROBLEMS OF HARMONIZATION OF NATIONAL STANDARDS AND GENERAL EUROPEAN ONES - Жмур, Наталія Володимирівна; Поліщук, Інна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: at the present stage of development of international civil aviation in the context of globalization and technical progress, the problem of liberalization of international and state regulation of civil aviation safety in the context of reducing the scope of state control of civil aviation is relevant. This is confirmed by the holding of two World Air Transport Conferences of the International Civil Aviation Organization (ICAO) in 2003 and 2013, which were specifically devoted to the problems of liberalization and the development of standards and mechanisms for its implementation. Given the spread of global trends in liberal relations in the field of civil aviation, there is a need to study the level of liberalization of national standards in the context of a particular country and their harmonization with European and world standards, developing a common strategy for civil aviation safety. The article considers the problems of harmonization of national standards and European ones of civil aviation security liberalization at the current stage of development of international civil aviation, identifies the impact of liberalization on national and European standards of air safety, airspace, ground handling and all aviation infrastructure. Particular attention is paid to the development of civil aviation security liberalization in Ukraine, the integration processes of state policy in this area. Research methods: general scientific and special methods of analysis and comparison are used in the work. Results: the conclusion is made about the need to improve the state regulation of civil aviation safety, providing the most favorable conditions and forms of cooperation in the field of liberalization of its safety, in particular, by improving national and international regulations. Discussion: finding ways to solve national problems of civil aviation security liberalization and the need to adapt it to international standards, integration and globalization processes, management principles and security.